Deconstructing the Learning Styles Myth in English Language Learning from the Perspective of Santrock's Educational Psychology for Evidence-Based Practice - Wesly Baan; Dylmoon Hidayat (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This literature review deconstructs the learning styles myth in English language teaching through Santrock's educational psychology framework. Many English teachers believe that aligning instruction with students’ dominant learning styles (visual, auditory, kinesthetic) improves the students' academic achievement. However, empirical evidence does not support this practice. This study employs a narrative literature review method to examine existing research on learning styles and evidence-based practices. This article deconstructs the learning styles myth by comparing it with evidence-based practices such as retrieval practice, spaced learning, formative assessment, and collaborative learning. Findings from global and Indonesian studies consistently highlight that evidence-based strategies consistently enhance retention, engagement, and achievement in English language learning. These insights are expected to encourage teachers in Indonesia to shift from myth-based paradigms toward more scientific, contextual, and effective teaching practices.